Potential impact of microbial activity on the oxidant capacity and organic carbon budget in clouds - Vaïtilingom, Mickael (National Academy of Sciences, 2013)
Within cloud water, microorganisms are metabolically active and, thus, are expected to contribute to the atmospheric chemistry. This article investigates the interactions between microorganisms and the reactive oxygenated species that are present in cloud water because these chemical compounds drive the oxidant capacity of the cloud system. Real cloud water samples with contrasting features (marine, continental, and urban) were taken from the puy de Dôme mountain (France). The samples exhibited a high microbial biodiversity and complex chemical composition. The media were incubated in the dark and subjected to UV radiation in specifically designed photo-bioreactors. The concentrations of H(2)O(2), organic compounds, and the ATP/ADP ratio were monitored during the incubation period. The microorganisms remained metabolically active in the presence of (●)OH radicals that were photo-produced from H(2)O(2). This oxidant and major carbon compounds (formaldehyde and carboxylic acids) were biodegraded by the endogenous microflora. This work suggests that microorganisms could play a double role in atmospheric chemistry; first, they could directly metabolize organic carbon species, and second, they could reduce the available source of radicals through their oxidative metabolism. Consequently, molecules such as H(2)O(2) would no longer be available for photochemical or other chemical reactions, which would decrease the cloud oxidant capacity.